ANALISIS KEKUATAN KOMPOSIT IJUK SEBAGAI BAHAN PENGGANTI FIBERGLASS PADA KAPAL - Muhammad Agam Thahir; Muhammad Arif Nasution; Hafinuddin Hafinuddin; Surya Bima Ridho Mutaqin (JURNAL PERIKANAN TROPIS, 2021)
AbstractThis study uses a quantitative experimental method using a Completely Randomized Design (CRD) with 2 treatments and 3 replications. The palm fibers composite was made by following the compression test standard of SNI 03-3958-1995 and the tensile test standard of ASTM D3039. The hand lay up method is used in the manufacture of composites by applying resin to the mold with a roller brush. The compression and tensile tests were carried out using the Gotech Testing Machine (GT 7001 LC 30). The results of the compression test of the palm fiber composite 909.19 Mpa, the tensile test 10.82 Mpa, based on the test results, a comparison was made with the BKI (Indonesian Classification Bureau) standard, it is known that the fiber composite can only meet the minimum standard of compressive strength determined by BKI 100 Mpa, while the value of the tensile strength has not been able to meet the minimum standard specified by BKI 150 Mpa.Keywords:  Fiberglass, palm fiber composite. compression test